2018
DOI: 10.35334/be.v2i2.617
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Bentuk Bukaan Atap Bangunan Terhadap Tingkat Kenyamanan Termal Pada Rumah Panjang Suku Dayak Brusu, Kecamatan Sekatak, Kalimantan Utara

Abstract: The long house of the Brusu Dayak tribe that lives in North Kalimantan is a house that always increases the length of the building following the increase in the number of family heads in one offspring. The most interesting part of the longhouse compared to other Dayak tribes' houses is that in the longhouse Brusu Dayak tribes do not have windows but only rely on openings on the roof of the building according to their residential needs so that it affects the thermal comfort of the longhouse. In general, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In Lamin's house, the roof serves as an element that dominates the house. The research found that the roof maximized heat transfer, as in the Brusu Dayak tribe living in North Kalimantan 22) and Betang Ensaid Panjang, the traditional Dayak house in Sintang Regency 23) . A research method includes direct surveys and measurements of several points in a traditional house, including measurements of temperature, humidity, and air movement 22,23) .…”
Section: Lamin House Passive Designmentioning
confidence: 94%
See 2 more Smart Citations
“…In Lamin's house, the roof serves as an element that dominates the house. The research found that the roof maximized heat transfer, as in the Brusu Dayak tribe living in North Kalimantan 22) and Betang Ensaid Panjang, the traditional Dayak house in Sintang Regency 23) . A research method includes direct surveys and measurements of several points in a traditional house, including measurements of temperature, humidity, and air movement 22,23) .…”
Section: Lamin House Passive Designmentioning
confidence: 94%
“…The thermal comfort of Lamin houses varies at different times in different spaces 22,23) . As a result, it can be classified as slightly cool in the morning, warm in the afternoon and evening, and comfortable at night.…”
Section: Lamin House Passive Designmentioning
confidence: 99%
See 1 more Smart Citation
“…While the experimental approach is carried out by measuring air temperature and humidity based on the group shape, orientation, and roof material. The measurement results are used to determine the effect of the shape, orientation, and material of the roof covering the thermal comfort level of households in KK [7] dan [8].…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini diterapkan pada rumah mereka yang disebut rumah Betang, dan rumah ini memiliki konsep persatuan didalam setiap keluarga yang harus terwujud agar dapat bertahan dari serangan musuh. Bentuk rumah yang sederhana tanpa memiliki bukaan atau ventilasi berupa jendela, rumah disampingnya sebagai rumah tinggal juga digunakan sebagai tempat acara-acara yang bersifat adat, ritual, dan sebagainya (Wahyudi, 2018). Tujuan tersebut menyebabkan ruang keluarga dibuat begitu besar agar memenuhi banyaknya anggota keluarga, walaupun pada perjalanan waktu terdapat beberapa perubahan seperti penempatan jendela akibat berkurangnya konflik antar Suku yang terjadi.…”
Section: Latar Belakangunclassified